FBMC Transmitters with Reduced Complexity - Z. Kollar; H. Al-Amaireh (Radioengineering, 2018)
Filter Bank MultiCarrier (FBMC) modulation is currently considered as one of the key enablers for future 5G technologies. In the literature, two approaches are applied for the modulation of FBMC signals: Frequency Spreading (FS) and PolyPhase (PP) implementation. The complexity requirements of FBMC transmitters is considered to be one of the key research fields. In this paper various FBMC implementations are compared in terms of complexity and quantization error. An alternative design approach is suggested: the two full size Inverse Fourier Transforms (IFFTs) in the standard PP can be replaced by two half size IFFTs taking advantage of real valued data processing. It is shown that the complexity of the design will be almost reduced by half. Furthermore, the proposed alternative method has the lowest quantization error among the investigated transmitter architectures, which is a key issue in hardware with low precision arithmetics.